Childhood Leukemia and Electromagnetic Fields - Alpaslan Türkkan (Güncel Pediatri)
In this review, the relationship between very low frequency electromagnetic fields, originating from high voltage powerlines, and childhood leukemia was evaluated. Electromagnetic fields have biological effects. Whole populations are effected by different levels of electromagnetic fields but children are more sensible. In urban areas high voltage powerlines are the main sources of electromagnetic fields. The relation of electromagnetic fields due to high voltage powerlines and leukemia with consideration of dose-response and distance is investigated in several studies. There are different opinions on the effects of electromagnetic fields on general health. The relation between electromagnetic fields and childhood leukemia must be considered separately. Although there is no limit value, it is generally accepted that exposure to 0.4 µT and over doubles the risk of leukemia in children 15 years and younger. (Journal of Current Pediatrics 2009; 7: 137-41)